The application of OLAP technology in the automated risk assessment system for oil and gas fields; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Zavyalov D. A. Dmitrii Alekseevich (2017, 2017)
Title screen